2016
DOI: 10.1021/acs.jpcc.6b02011
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of PDMS-Stamped Halide Perovskite Single Microcrystals

Abstract: Recently, halide perovskites have attracted considerable attention for optoelectronic applications, but further progress in this field requires a thorough understanding of the fundamental properties of these materials. Studying perovskites in their single-crystalline form provides a model system for building such an understanding. In this work, a simple solution-processed method combined with PDMS (polydimethylsiloxane) stamping was used to prepare thin single microcrystals of halide perovskites. The method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…With symmetric back-contact, such a device shows no obvious photovoltaic characteristics, demonstrating the importance of the nonsymmetric Schottky junction. The work function difference of the two contacts can be realized either by adopting different metals [126] or by surface polarity modification of metal electrode. [36] The device gives a V oc of 0.55 V (Figure 7j) and a highest performing bc-PSC showed a PCE of 3.11%.…”
Section: Lateral Structurementioning
confidence: 99%
See 3 more Smart Citations
“…With symmetric back-contact, such a device shows no obvious photovoltaic characteristics, demonstrating the importance of the nonsymmetric Schottky junction. The work function difference of the two contacts can be realized either by adopting different metals [126] or by surface polarity modification of metal electrode. [36] The device gives a V oc of 0.55 V (Figure 7j) and a highest performing bc-PSC showed a PCE of 3.11%.…”
Section: Lateral Structurementioning
confidence: 99%
“…Khoram et al reported a microscopic PSC based on single microcrystals perovskite grown on prefabricated grating electrodes with nonsymmetric work functions (Figure 7a,b) creating single-crystal devices contacted from the back (bc-PSC, Figure 7c-f). [126] Such a microscale PSC with high (Pd) and low (Ti) work function metals as carrier-selective contacts gives a high V oc of 1.07 V (Figure 7g). With symmetric back-contact, such a device shows no obvious photovoltaic characteristics, demonstrating the importance of the nonsymmetric Schottky junction.…”
Section: Lateral Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The photovoltaic properties of CTL-free PSCs, in which metals or graphene directly contact the perovskite to create Schottky junction solar cells [9][10][11][12][13][14] , depend strongly on the built-in potential established by the work function difference of the two contacts ( Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%